METODE PEMBELAJARAN E-LEARNING DENGAN MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODELING (TAM) UNTUK PEMBELAJARAN AKUNTANSI - Sri Hutami Adiningsih S; Is Arianto Pratama (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to develop an e-learning based learning model. By implementing e-learning learning design, both lecturers and students can more easily design and develop courses, especially those relevant to the needs of accounting learning in the Accounting Study Program, State University of Makassar. The main objective of this study is to identify factors that influenceThe success of e-learning through the Technology Acceptance Model (TAM) approach, encourages the optimization of e-learning utilization in the learning process, and increases the effectiveness of its use in the Makassar State University environment. The design of the e-learning learning system in this study refers to the TAM concept, which is a model that explains user acceptance of information technology systems. This model consists of five main constructs: perceived usefulness, perceived ease of use, attitude toward behavior, behavioral intention, and actual technology use. Hypothesis testing was carried out using the Structural Equation Modeling (SEM) method, through the stages of validity and reliability evaluation, model fit testing, latent construct coefficient analysis, and indirect and total effect testing. Of the seven hypotheses proposed, five were accepted, and other two hypotheses were rejected.